Effectiveness Behavioral Counseling Ivan Pavlov Modeling Techniques on Lesson Study Setting to Improve Allied Characters - Ni Luh Linda Seniasih; K Suranata; I Ketut Dharsana (RedwhitePress)
This study aims to determine the effectiveness of behavioral counseling Ivan Pavlov modeling to improve the character communion with others through lesson study in grade one. The research is a quasi-experimental design with pre-test, and post-test control group. A sample of 35 students with db 34.Method of data collection using questionnaire's character of communion with others with others as much as 30 items. The result of the data analysis is the value of tcount 2.71778 >ttable 1.69092. So Ho rejected and Ha accepted. So there is a significant difference. It can be concluded that the counseling behavioral Ivan Pavlov effective modeling to improve the character of communion with others.